Enhanced thermodynamic assessments of the novel desiccant air cooling system for sustainable energy future. (20th February 2019) - Caliskan, Hakan; Lee, Dae-Young; Hong, Hiki
Abstract: In this study, a newly developed desiccant air cooling system with desiccant wheel, sensible heat wheel and evaporative air cooler is assessed. The main purpose of the study is to investigate the developed desiccant air cooling system and compare its performance with the previous studies to show reliability of the developed system. The energy, exergy and sustainability analyses methods are used to assess the system. The data are obtained at 35 °C and 101.3 kPa environment condition. According to the exergy analysis, this system can be largely improved. The electrically and thermally driven energy coefficient of performance of the overall system (6.71 and 0.77) are higher than the corresponding exergy coefficient of performance (0.198 and 0.463). Energy coefficient of performance shows that the performance of the overall system is high, however electrically driven exergy coefficient of performance shows that some modifications can be realized in order to improve the final performance of the system. Among the components, desiccant wheel should be improved, because its exergy destruction ratio is 42.87% and the exergy efficiency is about 38.35%. On the other hand, sensible heat wheel exergy destruction ratio is computed as 10.35%, and its exergy efficiency is determined to be 57.69%. Among the components, desiccant wheel has less sustainability than others considering a combination work together. The effectiveness of the components from maximum to minimum are as sensible heat wheel, regenerative evaporative cooler and desiccant wheel, respectively. For better effectiveness, the component devices should be working around similar high level. So, the urgent improvements for the devices are in the order of desiccant wheel, regenerative evaporative cooler and sensible heat wheel, respectively. Graphical abstract: Highlights: Novel desiccant air cooling system with regenerative evaporative cooler. Energy, exergy and sustainability assessments. Comparison of a novel desiccant air cooling system with other. High performance for the novel desiccant air cooling system.